2010
DOI: 10.1103/physrevb.82.099903
|View full text |Cite
|
Sign up to set email alerts
|

Erratum:K2Cr8O16predicted as a half-metallic ferromagnet: Scenario for a metal-insulator transition [Phys. Rev. B80, 024416 (2009)]

Abstract: Figures 1 and 2 of our paper 1 should be replaced by Figs. 1 and 2 shown here, where O͑1͒ and O͑2͒ have been interchanged. Also, the last sentence of Sec. III A should read "Note that the O͑1͒ ions inside the double strings of Cr ions have a positive spin polarization, whereas the O͑2͒ ions connecting the double strings have a negative spin polarization." These changes do not affect the results of our paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 1 publication
6
22
0
Order By: Relevance
“…The number of d electrons thus indicates that the second band counted from the top in the t 2g manifold crosses the Fermi level with the filling of electrons roughly between a half to three quarters if the second band is isolated (although of course more than one band can cross the Fermi level). Our preliminary electronic structure calculations indicate that the band structure is not very simple but there is in fact a highly quasi-one-dimensional band, as expected from our results for K 2 Ru 8 O 16 , which is consistent with the quasi-one-dimensional transport properties reported in Ba [3] have shown that the system is a fully spin-polarized half metal and that the Fermi level is located between the third and fourth bands counted from the top of the t 2g manifold for majority-spin electrons, or that both of the third and fourth bands cross the Fermi level to form a semimetallic (or compensated metallic) band structure.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The number of d electrons thus indicates that the second band counted from the top in the t 2g manifold crosses the Fermi level with the filling of electrons roughly between a half to three quarters if the second band is isolated (although of course more than one band can cross the Fermi level). Our preliminary electronic structure calculations indicate that the band structure is not very simple but there is in fact a highly quasi-one-dimensional band, as expected from our results for K 2 Ru 8 O 16 , which is consistent with the quasi-one-dimensional transport properties reported in Ba [3] have shown that the system is a fully spin-polarized half metal and that the Fermi level is located between the third and fourth bands counted from the top of the t 2g manifold for majority-spin electrons, or that both of the third and fourth bands cross the Fermi level to form a semimetallic (or compensated metallic) band structure.…”
Section: Introductionsupporting
confidence: 79%
“…We thereby examine the 3d series (M =Ti, V, Cr, Mn) as well as the 4d series (M =Mo, Ru, Rh) to discuss generic features in the electronic structure of hollandites first. Then, we in particular study the quasi-one-dimensional electron conduction observed in K [2,3] is discussed in this respect. We also study the electronic structure of K 2 V 8 O 16 to consider the origins of the observed anomalous electronic states and metal-insulator transition [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, chromium hollandite K 2 Cr 8 O 16 , which has the Cr ions with the average valence of Cr 3.75+ , was found to show a very rare metal-insulator transition keeping the ferromagnetism unchanged [1][2][3][4][5]. A chromium oxide NaCr 2 O 4 is one of the mixed-valent chromium oxide, which was reported to exhibit a colossal magnetoresistance effect [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A novel MI transition from the FM metallic to the FM insulating phases was reported to take place at T MI =95 K in the FM state below T C =180 K in K 2 Cr 8 O 16 with a rare mixed valence of Cr 3+ :Cr 4+ =2:6 (3d 2.25 ) [6]. In particular, the mechanism of the MI transition has attracted much attention from the experimental and theoretical point of views [6,10]. In both oxides, the orbital degree of freedom plays an important role for the magnetic and electric properties.…”
Section: Introductionmentioning
confidence: 99%